(untitled) (Chittagong University Journal of Biological Sciences, 2013)
The present study has been taken to discuss the human dimension of the phenomenon and argues the need for a better understanding of the mechanisms underlying erosion-induced people at Haimchar upazila in Bangladesh. The paper emphasizes the importance and need for looking into the phenomena of riverbank erosion, course shifting tendency, population displacement and its impact in socio-economic condition at national scale in order to understand and competently deal with the problem. In this study both primary and secondary data have been used. The primary data include field survey and victims opinion survey from erosion-affected villagers through questionnaire. During the last three decades about 35,605 peoples were displaced in the study area due to river bank erosion. Most of the affected people were living on the embankment. It was noted that there is a great degree of uncertainty as to when land would be devoured by the river; and on an average people were affected 3 times during the last three decades. Some of the techniques to survival strategies for the affected households are also discussed in this study. DOI: http://dx.doi.org/10.3329/cujbs.v4i1.13384 The Chittagong Univ. J. B. Sci.,Vol. 4(1&2):25-39, 2009